Chronic respiratory dysfunction due to diaphragmatic paralysis following penetrating neck trauma: A case report. Issue 4 (29th January 2021) - Wang, Lian; Liu, Tianshu; Liu, Zhihai
Abstract: Rationale: Respiratory dysfunction resulting from unilateral diaphragmatic paralysis during neck trauma is very rare in adults. We describe the symptoms, diagnosis and treatment of 1 patient with chronic respiratory insufficiency, in whom the diaphragmatic paralysis was associated with phrenic nerve injury due to penetrating neck trauma. Patient concerns: A 50-year-old worker was admitted because of left penetrating neck trauma. Imaging investigations demonstrated elevation of the left hemidiaphragm and the C5 and C6 roots avulsion. He complained of gradually worsening dyspnea on exertion 2 months later. Diagnoses: The patient was diagnosed with chronic respiratory dysfunction secondary to diaphragmatic paralysis, which caused by phrenic nerve injury. Interventions: A conventional video-assisted thoracoscopic diaphragm plication was performed after failed conservative management. Outcomes: The respiratory status improved markedly, and he did well without recurrence until 2 years' follow-up. Lessons: The possibilities of phrenic nerve palsy and diaphragmatic paralysis should not be overlooked during the evaluation of neck trauma. Abstract : Supplemental Digital Content is available in the text